Buried Childhoods: Uncovering Illicit Child Labour in Madagascar’s Mica Mines - Manitra, Ramalina Ranaivo Mikea; Andriamiandrisoa Hoby Nasandratra; Andrianjafimalala Harifia Domoinaniaina Claudia Valerine; Lanja Manohisoa Epifaniah (Center for Law and Responsible Business Studies, 2025)
Around the world, child labour in the mining sector remains a grave human rights issue, disproportionately affecting impoverished communities in resource-rich yet economically marginalised regions. Madagascar is no exception, where thousands of children are engaged in hazardous mica mining under exploitative and unsafe conditions. This paper aims to critically examine the systemic use of child labour in Madagascar’s mica industry by analysing the findings of the NBC News documentary “Children Labor for Pennies Mining Mica in Madagascar” against the backdrop of relevant national and international legal frameworks. Employing a socio-legal method, the study assesses legal norms, policy instruments, and their implementation gaps to understand how legal obligations fail to translate into meaningful protections for children. The findings reveal widespread breaches of labour, mining, and child protection laws, including violations of the right to education, the prohibition of hazardous child labour, and the duty of state oversight. Despite the existence of robust legal provisions in the Labour Code, Child Protection Law, Mining Code, and Mining Permit Law, enforcement remains weak, particularly in informal and artisanal mining zones. Drawing from comparative policy experiences in countries like the United Kingdom, Burkina Faso, and the Democratic Republic of Congo, this paper recommends the adoption of binding corporate due diligence, formalisation of artisanal mining, and the establishment of cross-sectoral enforcement mechanisms to ensure that children are protected from exploitation across the mining value chain.